The influence of the modifying elements on the microstructure, mechanical, and deformation properties of aluminum alloys - Alzahrani, Mahmoud A.; Moustafa, Essam B.; Alsoruji, Ghazi; Mosleh, Ahmed O. (Frontiers in Materials, 2022)
In the current work, the standard A242 aluminum cast alloy is modified using the stir casting method with titanium (Ti) (0.5% wt.) and boron (B) (0.1% wt.) modifiers. Polarized optical and scanning electron microscopy were utilized to examine the A242 base microstructure, and A242 + TiB modified alloys; the results revealed that the modified A242 + TiB alloy was refined by 13.5 times more than the as-cast alloy. The mechanical properties were investigated experimentally using compression test in addition to the hardness test; the results revealed that the ultimate compressive strength of the A242 + TiB modified alloy was increased by 9.0% more than those of the A242 standard alloy. Moreover, the yield stress was enhanced by 40% at room temperature and 20% at 250 °C. The dynamic properties were studied using a free vibration impact test to study the modifiers’ effect on the dynamic behavior. The grain refinement notably impacted the damping capacity; due to the as-cast inhomogeneity, the conventional alloy A242 exhibited a greater FRF than the modified alloy A242 + TiB. The modified alloy displayed fewer resonance peaks due to grain refinement and excellent intermetallic phase distribution. The simulation process of the investigated alloys was performed using ABAQUS finite element software to predict the deformation behavior under different temperatures. The FE results showed that the modified alloy was more resistant to deformation by 9.1% than the reference alloy, A242, at room temperature and 7.6% at 250 °C, which agreed with the experimental findings.